2007
DOI: 10.1634/stemcells.2006-0432
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Regulate Angiogenesis According to Their Mechanical Environment

Abstract: The underlying mechanism appears to be dependent on the FGFR and VEGFR signaling cascades and might be mediated by an additional cross-talk with other pathways. STEM CELLS 2007;25:903-910 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
164
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(170 citation statements)
references
References 47 publications
(54 reference statements)
3
164
0
3
Order By: Relevance
“…42,43 Kasper et al showed that the conditioned medium from mesenchymal stem cells subjected to mechanical loading increased sprouting of endothelial cells by creating an angiogenic promoting environment. 44 Certainly other paracrine factors besides VEGF could also be playing a role in the improvement of cardiac function imparted by the MS MDSCs. For example, the conditioned medium of MS mesenchymal stem cells had an upregulation of MMP-2 and TGF-B1, 44 which is an area for future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Kasper et al showed that the conditioned medium from mesenchymal stem cells subjected to mechanical loading increased sprouting of endothelial cells by creating an angiogenic promoting environment. 44 Certainly other paracrine factors besides VEGF could also be playing a role in the improvement of cardiac function imparted by the MS MDSCs. For example, the conditioned medium of MS mesenchymal stem cells had an upregulation of MMP-2 and TGF-B1, 44 which is an area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…44 Certainly other paracrine factors besides VEGF could also be playing a role in the improvement of cardiac function imparted by the MS MDSCs. For example, the conditioned medium of MS mesenchymal stem cells had an upregulation of MMP-2 and TGF-B1, 44 which is an area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MSCs regulated angiogenesis according to their mechanical environment. Osteogenic proliferation and differentiation appeared when MSCs were stimulated by mechanical loading (Koike et al 2005;Yoshikawa et al 1997;Kasper et al 2007;Mauney et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the latter condition likely affects MSCs, which are known to be mechanosensitive (Wang and Thampatty, 2008). Thus, detailed knowledge about the infl uence of mechanical loading on MSCs is pivotal for understanding (Kasper et al, 2007a) and matrix remodelling (Kasper et al, 2007b) -key processes in bone regeneration. However, investigations regarding cell autonomous alterations in MSCs, specifi cally their MSC-characteristics and associated functional changes due to loading are still missing.…”
Section: Introductionmentioning
confidence: 99%